Small things like these (oprah's book club) ebook - Keegan, Claire (Grove Press, 2021)
**OPRAH'S BOOK CLUB PICK 2024** ** NEW YORK TIMES BOOK CLUB PICK 2024** NOW A MAJOR MOTION PICTURE STARRING CILLIAN MURPHY A New York Times Bestseller • Shortlisted for the 2022 Booker Prize • Winner of the Orwell Prize for Political Fiction One of the New York Times 's 100 Best Books of the 21st Century "A hypnotic and electrifying Irish tale that transcends country, transcends time." —Lily King, New York Times bestselling author of Writers & Lovers Small Things Like These is award-winning author Claire Keegan's landmark new novel, a tale of one man's courage and a remarkable portrait of love and family It is 1985 in a small Irish town. During the weeks leading up to Christmas, Bill Furlong, a coal merchant and family man faces into his busiest season. Early one morning, while delivering an order to the local convent, Bill makes a discovery which forces him to confront both his past and the complicit silences of a town controlled by the church. An international bestseller, Small Things Like These is a deeply affecting story of hope, quiet heroism, and empathy from one of our most critically lauded and iconic writers.